Using community maternity care assistants to facilitate family‐focused breastfeeding support - Ingram, Jenny (Matern Child Nutr, 2009)
Increasing breastfeeding rates, particularly in lower socio‐economic areas, would have considerable impact upon public health. Social support has been found to have direct and positive effects on breastfeeding rates, and fathers' attitudes have an important influence on the initiation and continuation of breastfeeding. In the UK, trained maternity care assistants (MCAs) are increasingly being used to support community midwives by providing post‐natal women with breastfeeding support. The current study aimed to evaluate the feasibility and acceptability of MCAs involving fathers from economically deprived communities in antenatal breastfeeding discussions to equip them to provide support and encouragement. Eleven couples who took part in the intervention were interviewed post‐natally. MCAs, midwives and midwifery managers gave their views on the intervention and role of MCAs in the community. The study showed that MCAs with appropriate training are very effective at delivering antenatal breastfeeding information, which both mothers and other family members value. MCAs found giving such breastfeeding support both enjoyable and fulfilling, while involving fathers and family members proved a practical way of encouraging them to be more supportive. Midwives and midwifery managers were positive about involving MCAs in giving the antenatal intervention, but did not see the routine introduction of this type of session for couples being possible at present due to current staffing problems. Involving fathers in breastfeeding support may start to increase knowledge and change attitudes towards breastfeeding in communities where formula feeding is seen as the normal way to feed a baby.